2010
DOI: 10.1590/s0036-46652010000600003
|View full text |Cite
|
Sign up to set email alerts
|

Profile of patients with Baggio-Yoshinari Syndrome admitted at "Instituto de Infectologia Emilio Ribas"

Abstract: SUMMARYThe aim of this study was to evaluate the epidemiological, clinical and laboratorial profile of patients with Baggio-Yoshinari Syndrome (BYS), who underwent internment at the Instituto de Infectologia Emilio Ribas in São Paulo, Brazil, during the period from July 1990 to July 2006. BYS is a new Brazilian tick-borne disease caused by Borrelia burgdorferi sensu lato microorganisms that resembles features of Lyme disease (LD), except for its epidemiological, clinical and laboratorial particularities. From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 32 publications
1
26
0
2
Order By: Relevance
“…In Brazil, a similar disease, referred as Brazilian Lyme diseasesimile illness or Baggio-Yoshinari Syndrome (BYS) has been described, since last ending century GOUVEIA et al, 2010). Mantovani et al (2007) were unable to confirm whether this syndrome is caused by new Borrelia species or it is related to genetically modified Borrelia burgdorferi sensu lato microorganisms or other infectious agent.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, a similar disease, referred as Brazilian Lyme diseasesimile illness or Baggio-Yoshinari Syndrome (BYS) has been described, since last ending century GOUVEIA et al, 2010). Mantovani et al (2007) were unable to confirm whether this syndrome is caused by new Borrelia species or it is related to genetically modified Borrelia burgdorferi sensu lato microorganisms or other infectious agent.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, the study of LD started in 1989 and until now much of the knowledge on Brazilian borreliosis is due to the research effort of a multidisciplinary team headed by Dr. Natalino H. Yoshinari 68 , 71. In a preliminary study of 19 patients, Yoshinari and coworkers found that 31.5% had skin lesions, 31.5% had arthritis, and 42% had neurological disorders 70.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory diagnosis of BYS is difficult because serological tests (ELISA, enzyme immunosorbent assay, or western blotting) for B. burgdorferi show low sensitivity and specificity27, 28, 29, 30, 31, 32; this is because these tests utilize antigens from B. burgdorferi stricto sensu from the Northern Hemisphere to evaluate immunoglobulins of Brazilian B. burgdorferi sensu lato.…”
Section: The Disease In Humans (Ld Of the Northern Hemisphere Versus mentioning
confidence: 99%